2021
DOI: 10.1136/gutjnl-2020-323297
|View full text |Cite
|
Sign up to set email alerts
|

Duodenal Anaerobutyricum soehngenii infusion stimulates GLP-1 production, ameliorates glycaemic control and beneficially shapes the duodenal transcriptome in metabolic syndrome subjects: a randomised double-blind placebo-controlled cross-over study

Abstract: ObjectiveAlthough gut dysbiosis is increasingly recognised as a pathophysiological component of metabolic syndrome (MetS), the role and mode of action of specific gut microbes in metabolic health remain elusive. Previously, we identified the commensal butyrogenic Anaerobutyricum soehngenii to be associated with improved insulin sensitivity in subjects with MetS. In this proof-of-concept study, we investigated the potential therapeutic effects of A. soehngenii L2-7 on systemic metabolic responses and duodenal t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
26
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 28 publications
(30 citation statements)
references
References 67 publications
(78 reference statements)
1
26
0
Order By: Relevance
“…Moreover, duodenal perfusions of live or dead Lactobacillus spp have been found to affect the host immune response, providing an experimental system for human discovery 27–29. This has been recently exploited for the analysis of a single duodenal dose of Anaerobutyricum soehngenii (previously known as Eubacterium hallii )30 that increased the duodenal expression level of the gene for regenerating islet-protein 1B almost 10-fold and also increased serum glucagon-like peptide-1 (GLP-1) and secondary bile salts in metabolic syndrome subjects, thereby potentially explaining their improved response to glucose 31 32…”
Section: The Human Gut Microbiomementioning
confidence: 99%
“…Moreover, duodenal perfusions of live or dead Lactobacillus spp have been found to affect the host immune response, providing an experimental system for human discovery 27–29. This has been recently exploited for the analysis of a single duodenal dose of Anaerobutyricum soehngenii (previously known as Eubacterium hallii )30 that increased the duodenal expression level of the gene for regenerating islet-protein 1B almost 10-fold and also increased serum glucagon-like peptide-1 (GLP-1) and secondary bile salts in metabolic syndrome subjects, thereby potentially explaining their improved response to glucose 31 32…”
Section: The Human Gut Microbiomementioning
confidence: 99%
“… 59 However, it is the acute response and contribution of GLP-1 to insulin regulation that is traditionally studied in oral glucose and meal challenges. In this context, the probiotic strains Limosilactobacillus reuteri SD5865 (formerly Lactobacillus reuteri ) and Anaerobutyricum soehngenii CH106 have been shown to beneficially increase acute postprandial GLP-1 response following oral supplementation and duodenal infusion, respectively, in clinical trials, 60 , 61 as well as other strains in animal studies. 62 , 63 Many clinical trials of probiotic supplementation have shown direct benefits on blood glucose control in patients with diabetes.…”
Section: Discussionmentioning
confidence: 99%
“…Importantly, the probiotic could be detected in stool samples provided by the recipients, suggesting survival through the gastrointestinal tract, and was deemed safe. Duodenal infusion of A. soehngenii in individuals with metabolic syndrome revealed that it stimulated the insulinotropic hormone glucagon-like peptide 1 production and increased expression of regenerating islet-protein 1B (Koopen et al, 2021).…”
Section: Health/disease Implicationsmentioning
confidence: 99%